Pesantren Ecotheology-Based Environmental Management: A Case Study of Pondok Pesantren in Lombok, Indonesia - Abdul Hayyi Akrom; Phaosan Jehwae; Zulkarnain Zulkarnain; Nur Azizah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study examines how Islamic eco-theological values are translated into environmental management practices in an Indonesian pesantren. The case of Pondok Pesantren Nurul Haramain was selected because its long-standing environmental initiatives, including reforestation, seedling nurseries, waste management, and ecological education provide a concrete setting for examining how religious values become institutional environmental practices. The study addresses a gap in the literature by analyzing not merely the normative presence of Islamic environmental values, but the institutional process through which these values are interpreted, legitimized, and transformed into managerial practices. Using a qualitative case study design, data were collected through semi-structured interviews, participant observation, and document analysis, and were examined through thematic analysis. The findings reveal four interconnected dimensions of pesantren-based environmental management: theological legitimation through the concepts of khalifah, amanah, and mizan; role-model leadership by religious authorities; environmental education through curriculum, habituation, and learning spaces; and material ecological practices such as greening, seedling distribution, and waste management. The study contributes to Islamic education, pesantren studies, and faith-based environmental governance by conceptualizing pesantren environmental management as an institutional process that connects theology, authority, pedagogy, and ecological praxis.